The Role of ChatGPT in Orthodontics: A Game Changer in Patient Engagement and Education (Academia Journal of Medicine, 2023)
ChatGPT, an AI chatbot, has the potential to  revolutionize the field of orthodontics by providing  valuable support to orthodontists, staff, and patients.  By leveraging its natural language processing  capabilities, ChatGPT can assist in several ways,  including answering patient questions, providing  educational information about orthodontic  treatments, offering post-treatment guidance, and  even supporting staff in managing administrative  tasks. The implementation of ChatGPT in orthodontic  practices can improve patient satisfaction, streamline  communication, and ultimately enhance the overall  orthodontic experience for both patients and  practitioners. This abstract provides an overview of the  role of ChatGPT in orthodontics and highlights its  potential impact on the field.
Keywords: ChatGPT; Artificial intelligence; Orthodontics